2021
DOI: 10.1007/s10811-021-02552-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the independent and combined effects of copper and polycyclic aromatic hydrocarbons on gametogenesis and sporophyte development of the kelp Lessonia spicata (Phaeophyceae, Ochrophyta)

Abstract: Coastal shores near the industrial park of Quintero Bay in central Chile exhibit increasing concentrations of copper (Cu) and polycyclic aromatic hydrocarbons (PAHs), well above international standards. This raises concern about their combined toxic effects on early development stages of kelps. Accordingly, we aimed to assess more accurately the independent and combined effects of Cu and PAHs on gametogenesis and sporophyte development in the kelp Lessonia spicata from central Chile by in vitro cultivation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Little information is available in the current literature on the capacity of PAHs to become bioconcentrated in this species. However, several deleterious effects in terms of sporulation, settlement, and germination were recently identified in this kelp and in Lessonia spicata exposed to Cu, Cd, and PAHs, as well as their binary and tertiary mixtures [16,17,42]. Conversely, it has been documented that individual M. pyrifera detached from the substrate can be passively dispersed over long distances, transporting both adhered animal species and algae; these detached algae are able to survive during drifting and develop reproductive structures [43,44].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Little information is available in the current literature on the capacity of PAHs to become bioconcentrated in this species. However, several deleterious effects in terms of sporulation, settlement, and germination were recently identified in this kelp and in Lessonia spicata exposed to Cu, Cd, and PAHs, as well as their binary and tertiary mixtures [16,17,42]. Conversely, it has been documented that individual M. pyrifera detached from the substrate can be passively dispersed over long distances, transporting both adhered animal species and algae; these detached algae are able to survive during drifting and develop reproductive structures [43,44].…”
Section: Introductionmentioning
confidence: 96%
“…These pollutants may negatively affect the organisms by decreasing successful reproduction or even causing death [14]. The bioavailability of HMs is influenced by environmental factors such as temperature, pH, salinity, solubility, and, in some cases, the presence of (and interaction with) other HMs [15][16][17]. Their toxicity is primarily related to the induction and generation of reactive oxygen species (ROS) through the Haber-Weiss reaction, which can cause damage to cellular components, such as DNA, lipids, proteins, and organelles [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the study found a 350% increase in hydrocarbon-oxidizing bacteria on the thalli of the algae when exposed to the diesel-water mixture. Another intertidal kelp species ( Lessonia spicata ) was found to be sensitive to PAHs especially during the sporophyte formation, with the EC 50 for the inhibition of the formation of sporophytes being 0.04 µg/L PAH EPA16 though this species might be particularly susceptible to reactive oxygen species which are created in photosynthetic organisms when exposed to PAHs (Espinoza-González et al 2021 ). As a primary producer and a foundation species, Fucus is a food source and an important habitat for many invertebrate species like Idotea balthica or Tonina fluviatilis , especially in the form of shed detritus.…”
Section: Discussionmentioning
confidence: 99%